Cowpea bean production under water stress using hydrogels - Marília Barcelos Souza Lopes (Pesquisa Agropecuária Tropical, 2017)
The population increase and the need of intensifying food production, coupled with the scarcity of water resources, have led to the search of alternatives that reduce consumption and optimize the water use during cultivation. In this context, hydrogels become a strategy in agricultural management, due to their water retention capacity in the soil and availability to plants. This study aimed at evaluating the efficiency of hydrogels on the development and production of cowpea bean (‘Sempre-verde’ cultivar) under water stress, in a greenhouse. The experiment was performed in a randomized block design, with five replications, in a 4 x 5 factorial scheme, consisting of four types of hydrogel (Hydroplan-EB HyA, with granulometry of 1-3 mm; Hydroplan-EB HyB, with granulometry of 0.5-1 mm; Hydroplan-EB HyC, with granulometry < 0.5 mm; Polim-Agri, with granulometry of 1-0.5 mm) and five concentrations (0 g pot-1; 1.5 g pot-1; 3 g pot-1; 4.5 g pot-1; 6 g pot-1). The following traits were evaluated: number of pods per plant, number of grains per pod and grain yield. The highest concentration (6 g pot-1) resulted in a higher number of pods and yield for all the hydrogels, especially for HyC and Polim-Agro, which presented 7.4 pods plant-1 and 7.0 pods plant-1, with yield of 15.43 g plant-1 and 16.68 g plant-1, respectively. The use of hydrogel shows to be efficient for reducing yield losses under water stress.